A variety of exact solutions to (2+1)-dimensional schrödinger equation. Issue 3 (2nd July 2020) - Younis, Muhammad; Cheemaa, Nadia; Mehmood, Syed Amer; Rizvi, Syed Tahir Raza; Bekir, Ahmet
ABSTRACT: The article investigates that the ( 2 + 1 ) -dimensional Schrödinger equation admits a rich variety of exact solutions with the range of five parameters. The solutions are of qualitatively different nature, depending on the different values of parameters. The obtained solutions are of triangular-type, soliton-type, doubly periodic-like, single and combined non-degenerate jacobi elliptic function like. Additionally, the constraint conditions for the existence of the solutions are also emerged during the derivation. The important fact of using the extended Fan sub-equation method is to take the full advantage of clear relationship among general elliptic equation involved with five parameters and other existing sub-equations involved with three parameters.